Mental Toughness in Students: A Descriptive Review - Sabila Fatima Zahra; Gian Sugiana Sugara; Cucu Arumsari (Edupotensia Foundation, 2026)
This study aims to describe the level of mental toughness of students at SMA Negeri 7 Tasikmalaya in facing academic failure. The study used a quantitative approach with a descriptive design. The study sample consisted of 213 students selected using a purposive sampling technique. The instrument used was the Adolescence Mental Toughness Scale, which measures three main aspects: persistence and growth orientation, emotional dysregulation, and self-resilience. The results showed that most students were in the medium (46.01%) and low (32.39%) categories of mental toughness, while others were in the high (14.08%) and very low (7.52%) categories. Based on the mental toughness aspects, the lowest scores tended to appear in the emotional dysregulation aspect, while relatively better scores were found in the persistence and growth orientation aspects. These findings indicate that although some students are able to maintain effort in facing academic demands, there are still vulnerabilities in managing emotions and the ability to recover from failure, making student mental toughness an important aspect that requires attention in the educational context